Effect of antifreeze protein on the quality and microstructure of frozen chicken breasts. (15th March 2023) - Chen, Junlin; Fan, Yaqi; Zhang, Xingguo; Yuan, Zimeng; Zhang, Hairu; Xu, Xinglian; Qi, Jun; Xiong, Guoyuan; Mei, Lin; Zhu, Yuan; Yang, Linwei; Li, Chao
Graphical abstract: Highlights: AFP played a positive role in maintain the quality of frozen chicken. Pretreatment with AFP reduced drip loss in chicken upon cryopreservation. 0.20% AFP retarded protein of chicken during freezing. 0.25% AFP slowed the damage of chicken myofibrils caused by large ice crystals. Abstract: The cryo-protective effects of different concentrations of antifreeze protein (AFP, 0 %, 0.10 %, 0.15 %, 0.20 %, 0.25 %, w/v) on chicken frozen at −18 °C for different storage perispeeods were investigated by monitoring water holding capacity (WHC), water distribution, color, protein properties, microstructure and histological changes. The results showed that AFP significantly maintained the quality traits of frozen chicken. Treatment with 0.20 % AFP represented highest cryo-protective effect on the WHC and protein properties during frozen storage. The carbonyl content with 0.20 % AFP was significantly lower than that of without AFP ( P < 0.05). Besides, the myofibrils of chicken supplemented with AFP, especially with 0.25 % AFP, had significantly tighter microstructure, smaller ice crystal area and equivalent diameter than those of without AFP treatment ( P < 0.05) after 75 d freezing storage. Overall, AFP had a positive effect to improve the quality of frozen chicken, and it was a potential, safe and efficient cryo-protective agent.